Effect of paclobutrazol on growth performance and yield of roselle ( Hibiscus sabdariffa L. ) - Buyamin, Nabila Huda (2015)
This research was conducted to investigate the effect of different concentration of paclobutrazol on growth performance and yield of roselle (Hibiscus Sabdariffa L.). The study was done under controlled environmental structure (CES) at Universiti Putra Malaysia, Serdang, Selangor. The experiment consisted of three concentration of paclobutrazol, T0- 0 ppm, T1- 100 ppm and T2- 200 ppm paclobutrazol. Soil media 2:2:1 was used as the planting media. The total numbers of plants are 60. Each treatment was replicated 4 times with 5 single plants in each treatment. The experimental design was Completely Randomized Design (CRD). Data on growth parameters (plant height, number of branches, total leaf area, internode length, fresh and dry weight of shoot and root and chlorophyll content) were collected from each treatment. For final harvest, yield analysis of fruit number, fruit fresh weight, weight of fresh calyx, weight of dry calyx, total soluble solid (TSS), ascorbic acid content and tissue analysis NPK content for shoot and root were taken from each plant. Data were analysed statistically by using Analysis of Variance (ANOVA) and mean comparison among treatments was performed using LSD test at probability 0.05. There were significant difference on data growth and yield parameters. For data growth parameter, the plants that applied with paclobutrazol showed lower growth compared to controlled plant. Meanwhile the yield in treatment 1 (100 ppm), for fruit number fruit number showed no significant different compared to controlled plant growth. Moreover, this study showed that plants that applied with paclobutrazol give greater total soluble solids value compared to controlled plants. While ascorbic acid content did not give any significant difference. As conclusion, there were differences in plant growth and nutrient uptake ability between controlled and both treatments. Since the treatment 1 (100 ppm) plant achieved same number of fruit compared to controlled plants, it is better to use 100 ppm paclobutrazol treatment applied to plants because to provide better resistance to lodging without loss of fruit yields and save labour costs for maintaining the plants.